Case Report: Remarkable breakthrough: successful treatment of a rare intracranial mesenchymal, FET::CREB fusion-positive tumor treated with patient-tailored multimodal therapy - D’Antonio, Federica; Rossi, Sabrina; Giovannoni, Isabella; Alaggio, Rita; Carai, Andrea; Milano, Giuseppe M.; Cacchione, Antonella; Cancellieri, Alessandra; Gessi, Marco; Antonelli, Manila; Colafati, Giovanna S.; Megaro, Giacomina; et al. (Frontiers in Oncology, 2023)
Background: Intracranial mesenchymal tumor is a rare mesenchymal tumor (0.3% of all soft tissue tumors) characterized by a fusion of a FET family gene (usually EWSR1, rarely FUS) to CREB family genes (CREB1, ATF1, and CREM) with a slow-growing and favorable prognosis. Mesenchymal tumors are most frequently localized in the sub-cutaneous tissue (typically in the limbs and the hands) of young adults and rarely have been diagnosed in the central nervous system. Surgery is the gold standard treatment; adjuvant radiation therapy and chemotherapy with sarcomabased regimens have been used in rare cases when complete surgical excision was not recommended. In terms of prognosis, these tumors show a tendency for local relapse. The most long-term patient outcomes reported in the literature are five years. Case description: This case describes a 27-year-old woman with unconventional extracranial metastatic sites of myxoid intracranial mesenchymal tumor FET::CREB fusion-positive and high expression of PD-1 (40%) and PD-L1 (30%). Based on clinical, molecular, and histological characteristics, she underwent various local and systemic therapies, including surgery, protonbeamtherapy, use of immune checkpoint inhibitors, and chemotherapy. These treatments led to a complete remission of the disease after eight years from tumor diagnosis. Conclusions: Our case sheds light on the importance of precision medicine and tailored therapy to explore new treatment opportunities for rare or unknown tumor entities.